Service Quality, Trust and Customer Satisfaction on Customer Loyalty: A Study of Banks in Malaysia - Chen, Kai (2012)
Conventional banking channels have been established including Automated Teller Machines (ATM), phone banking, and online banking, as well as increasingly mature financial markets and international competition have required banks to focus on the importance of customer loyalty. Therefore, the shifting position of financial sector together with the dynamic market have aroused researchers’ interest. It is of the essence that banks determine their level of customer satisfaction, complaint handling and customer loyalty to improve their competitive strength and identity problems to why customer churn or switch. It is expected that this study could contribute to the future banks practice and adopted to achieve customer loyalty level. The aim of the research is to test the extent of service quality level, complaint handling level, trust level and customer satisfaction level impact on customer loyalty level in Malaysian banks. A quantitative study was structure using a survey with a target of 250 respondents, then using Statistical Package for Social Science (SPSS) to analyze the data. The results showed service quality, trust and customer satisfaction have positive relationship with customer loyalty in Malaysia banking sector. However the complaint handling showed no relationship with customer loyalty, while customer satisfaction is the most important factor to influence customer loyalty.